2018
DOI: 10.1007/s12272-018-1088-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Carnosol on UVB-induced inflammation via inhibition of STAT3

Abstract: Ultraviolet B (UVB) irradiation causes sunburn, inflammatory responses, dysregulation of immune function, oxidative stress, DNA damage and photocarcinogenesis on skin. Rosemary (Rosmarinus officinalis L.) has been reported to inhibit inflammation. Carnosol, a major component of Rosemary, has prominent anti-inflammatory effects. However, its protective effect on UVB-induced inflammatory skin responses has not yet been reported. Here, we investigated the effectiveness of carnosol on UVB-induced inflammation. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 46 publications
(48 reference statements)
0
17
0
Order By: Relevance
“…This UVB-induced photodamage results from acute inflammatory responses, such as an increase in proinflammatory cytokines (e.g., IL-6 and IL-1 β ) [ 4 , 12 , 13 ], and the blood and lymphatic vasculature play an important role in the progression of inflammation. UVB irradiation induces vascular hyperpermeability and blood vessel dilation via production of prostaglandin E2 (PGE2) [ 14 ], resulting in increased extravasated fluid including excess water, macromolecules, and inflammatory cells.…”
Section: Introductionmentioning
confidence: 99%
“…This UVB-induced photodamage results from acute inflammatory responses, such as an increase in proinflammatory cytokines (e.g., IL-6 and IL-1 β ) [ 4 , 12 , 13 ], and the blood and lymphatic vasculature play an important role in the progression of inflammation. UVB irradiation induces vascular hyperpermeability and blood vessel dilation via production of prostaglandin E2 (PGE2) [ 14 ], resulting in increased extravasated fluid including excess water, macromolecules, and inflammatory cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that carnosic acid and, which are the most abundant compounds in R. officinalis leaves, considerably reduce the expression of IL-1β, TNF-α, and COX-2 [10]. In one study, it was shown that carnosol extracted from R. officinalis had anti-inflammatory and anti-fibrotic effects against ultraviolet B irradiation-induced skin inflammation, fibrosis, erythema, and epidermal thickness in HR1 mice through decreased activation of STAT3, a transcriptional factor regulating inflammatory genes [11].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-allergic effect of carnosol has also been observed in other Th2 cell-related diseases. In skin pharmacology, topical application of carnosol has been reported in PMA-induced ear edema, phthalic anhydride-induced atopic dermatitis, and UVB-induced inflammation ( Mengoni et al ., 2011 ; Lee et al ., 2017 ; Yeo et al ., 2019 ). Carnosol reduced the expression of IL-1β and TNF-α and inhibited COX-2 in PMA-induced ear inflammation in vivo ( Mengoni et al ., 2011 ).…”
Section: Discussionmentioning
confidence: 99%